Development of a project based learning model with multiliteracy pedagogic content to improve critical thinking skills, problem solving skills, decision making skills, and environmental literacy - Agustira, Deden; Al-Muhdhar, Mimien Henie Irawati; Lestari, Sri Rahayu; Pratiwi, Rani Tania (Edelweiss Applied Science and Technology, 2025)
This study explores the development of a Project-Based Learning (PBL) model incorporating multiliteracy pedagogy to enhance students' critical thinking, problem-solving, decision-making skills, and environmental literacy. The research is motivated by the increasing environmental issues caused by human behavior, particularly excessive consumption patterns and unsustainable habits among students. Addressing these challenges requires an education system that fosters environmental awareness and essential 21st-century skills. The study employs a Research and Development (R&D) approach using the Dick, Carey, and Carey instructional design model. The research is conducted in junior high schools through three phases: pre-development, development, and post-development. Data collection involves both qualitative and quantitative methods, including expert evaluations, student feedback, and statistical analyses of learning outcomes. A control-experiment design is employed to assess the suggested model's efficacy. The results show that using the PBL paradigm with multiliteracy pedagogy significantly improved students' critical thinking, problem-solving, decision-making, and environmental literacy. The model's ability to promote greater environmental responsibility and cognitive engagement was demonstrated by the experimental group's higher N-Gain score when compared to the control group. The data's validity and reliability were validated by statistical analysis, which revealed a significant difference (p < 0.05) between the pretest and posttest results. This study emphasizes how crucial it is to combine PBL with multiliteracy teaching in order to improve students' overall development. The implications suggest that educators should adopt innovative learning strategies to cultivate students’ environmental literacy and higher-order thinking skills, preparing them for future challenges in sustainable living and decision-making.